Application of photoelectrochemical oxidation of wastewater used in the cooling tower water and its influence on microbial corrosion - Kokilaramani, Seenivasan; Satheeshkumar, Alagersamy; Nandini, M. S.; Narenkumar, Jayaraman; AlSalhi, Mohamad S.; Devanesan, Sandhanasamy; Natarajan, Prabhu Manickam; Rajamohan, Rajaram; Rajasekar, Aruliah; Malik, Tabarak (Frontiers in Microbiology, 2024)
Background: Cooling towers are specialised heat exchanger devices that use air and water in close proximity to one another to cool the water's temperature. However, the cooling water contains organic nutrients that can cause microbial corrosion (MC) on the metal surfaces of the tower. To mitigate pollutants and prevent MC, this research explores the combined wastewater treatment approach using electro-oxidation (EO), photo-oxidation (PO), and photo electrochemical-oxidation (PEO).The study employed electro-oxidation, a process involving a Direct Current (DC) power supply, to degrade wastewater. MC studies were conducted using weight loss assessments, Scanning Electron Microscopy (SEM), and X-Ray Diffraction (XRD).Results: After treating the wastewater with electro-oxidation for a duration of 4 hours, a notable decrease in pollutants was observed, with degradation efficiencies of 71%, 75%, and 96% respectively. Wastewater treated with PEO restricts microbial growth by decreasing the chemical oxygen demand.Discussion: A metagenomics study revealed that bacteria present in the cooling tower water comprised 12% of Nitrospira genus and 22% of Fusobacterium genus. Conclusively, PEO serves as an effective method for treating wastewater, inhibiting microbial growth, degrading pollutants, and protecting metal from biocorrosion.